A1180V of Cardiac Sodium Channel Gene (SCN5A): Is It a Risk Factor for Dilated Cardiomyopathy or Just a Common Variant in Han Chinese? - Shen, Cheng (Hindawi Publishing Corporation, 2013)
Our previous study of a Chinese family with dilated cardiomyopathy (DCM) suggested that A1180V of the cardiac sodium channel gene (SCN5A) was associated with the disease within this family. According to data deposited in dbSNP, however, A1180V has been found in some small samples of the Asian population. In this study, we followed up the affected pedigree and expanded the investigation of the prevalence of A1180V in 460 unrelated healthy Han Chinese. Besides, we searched and analyzed it in other database as well. During the follow-up period, 1 A1180V carrier's condition deteriorated alot, and another 4 carriers progressed to DCM or atrioventricular block (AVB). We also found that the A1180V was absent among the 460 individuals (0%, 0/460), and the carrier frequency of A1180V among Chinese was about 0.51% obtained from the 1000 genome project. In conclusion, our finding suggests that A1180V is a potential risk factor for DCM, and it is extremely rare among Healthy Han Chinese.